Encapsulation of Fullerenes: A Versatile Approach for the Confinement and Release of Materials Within Open-Ended Multiwalled Carbon Nanotubes - Sandoval, Stefania; Tobias, Gerard (Frontiers in Bioengineering and Biotechnology, 2021)
We have employed fullerenes as versatile agents to “cork” the open tips of multiwalled carbon nanotubes (MWCNTs), and as promoting species for the release of the inorganic material filled within the nanotubes' cavities. High Z element compounds, namely, PbI2, ZnI2 and CeI3, were chosen to easily determine the presence of the filler inside the hosting nanotubes by transmission electron microscopy. Fullerenes can isolate inorganic nanostructures confined within the hollow cavities of MWCNTs, which allows the removal of the external material remnant after the filling. Otherwise, taking advantage of the affinity of fullerenes with selected solvents, we have confirmed the ability of the C60 molecules to promote the displacement of the inorganic guest from the host. We propose two different strategies to trigger the release, employing vapor and liquid phase treatments. The first protocol involves annealing filled MWCNTs in presence of fullerenes (to obtain C60PbI2@MWCNTs) and the subsequent washing of the sample in ethanol under mild conditions. On the other hand, the simultaneous introduction of the C60 molecules and the liberation of the guest are produced by a single step wet procedure; the latter being potentially useful when materials that are not stable at high temperatures are employed for filling.